ICT-ENHACED ELT FOR PHILOSOPHICAL LITERACY IN ISLAMIC EDUCATION: ADAPTING PRE-SOCRATES CONCEPTS AT PESANTREN LUHUR BAITUL HIKMAH KEPANJEN MALANG - Kholid, Moh; Heriyawati, Dwi Fita (Fakultas Ilmu Budaya, Universitas Mulawarman, 2026)
This study explores how Information and Communication Technology (ICT)-enhanced English Teaching (ELT) can foster philosophical literacy in Indonesian Pesantren by contextualizing pre-Socrates concepts within Islamic education. While existing ICT-ELT models focus primarily on linguistic skill, they rarely integrate abstract reasoning or cross-cultural epistemologies. Using a qualitative descriptives approach, this research involved interviews with teachers, classroom observations, and student reflection across three ICT-equipped Pesantren. Findings reveal that tools such as PPT slide presentation and collaborative platforms can effectively bridge Pre-Socratic themes—such as Heraclitus’s logos or Empedocles’s elemental dualism—with Islamic principle like tawhid. Educators adapted digital strategies to facilitate critical thinking, synthesis, and contextual engagement, while addressing cultural sensitivities. The study proposes an interdisciplinary pedagogical model that aligns with Pesantren’s religious ethos and global educational demands. This contributes to decolonial education discourse and offers scalable frameworks for faith-based ELT innovation in the Global South.